Analyzing the Rationality of Criminal Sanctions for Copyright Offences in Indonesia's Creative Economy - Putri Rumondang Siagian; Widad Azzuhdi Manurung (Faculty of Law, University of Merdeka Malang, 2026)
Copyright infringement in Indonesia causes economic losses to creators and copyright holders while threatening the sustainability of the creative economy. To address this issue, Law No. 28 of 2014 provides criminal sanctions for certain copyright infringements. However, the use of criminal law remains controversial, particularly regarding the principles of ultimum remedium, proportionality, and the objectives of criminalisation. This study analyses the construction of copyright offences in Indonesian law, their relationship with creative economy protection, and the rationality of criminal sanctions based on the theory of the purpose of criminalisation. Using normative legal research with statutory, conceptual, and policy approaches, the study analyses primary, secondary, and tertiary legal materials through qualitative legal interpretation. The findings show that criminalisation is justified to protect the economic value of intellectual works and support the sustainability of the creative industry. Nevertheless, criminal sanctions should be applied selectively to serious, commercial infringements causing significant harm, consistent with the principle of ultimum remedium. The novelty of this research lies in examining copyright offences through the rationality of the purpose of criminalisation as a balanced instrument for protecting the creative economy, beyond conventional analyses of copyright protection and law enforcement effectiveness.